Evolutionary genetic algorithm as a generative tools in identifying Malay, Chinese and Indian cultural product DNA / Izzuddinazwan Misri - Misri, Izzuddinazwan (2015)
Malaysia is the country that contained with the races, inherits, beliefs, religion of variety and also the culture itself. As the constitution has been made since 1957 and refined in 1963 until the era of 1 Malaysia, there a lot of effort that been made and proposed such consistency in languages and fairness in the determination of the rights of citizens to achieve the understanding and unity among societies in the country. In the expectancy at the enrichment of agreements,here are the designers should take a place in the adaptation of surroundings and today’s trend and issues. Culture itself makes the identity of races and this is the internal values of the country in addition to the community.As the influence to appreciation about culture and design collaborates, Scandinavians design has successfully established itself since 20th century (Esporadottir, 2011) also the design association NPO (DA) by Japanese designers expected and later succeed innovates idea among cultures that change the country through design. This unity that can be made by designing expose an idea to propose and making design DNA for Malaysia since they are only established in symbols, crafts, arts in recognizing the country identity. Furthermore, there is no official study in Malaysia being done in relation to design and the formulation to generate identity and DNA. This thesis presents an inquiry into the hybrid cross-cultural features of 3 majority races in Malaysia such the Malay, Chinese, and Indian using optimization tools called Genetic Algorithm in order to achieve new design DNA. It includes product categorizing of 3 races which organized by adapting the cross-cultural features measurement from Lin. R.T (2007) and these inform the development of a theoretical for assisting new design DNA transformation. A formal model of exploration is proposed with two mechanisms which encoded for product shapes and elements and decoded of gene types. This model is applied using visual representations which reveal new strategies for systematic new DNA generation and exploration in design.